Automotive CVT Sheave Development using Complex Forging Processes - Kun Peng, Wen; Park, Sung-Young (International Journal of Engineering and Technology, 2018)
Background/Objectives: In this study, we developed a complex forging process to produce a sheave, which is a core part of CVT for automobiles, fabricated prototypes. The existing processes such as hot forging and the MCT machining process have disadvantages including excessive amounts of material cutting, number of processes, and processing time.Methods/Statistical analysis: To overcome these shortcomings, in this study, a shape was created using hot forging and the shape was molded into a precision part using cold forging. A complex forging process was developed that enabled maximization of the metallographic density and reduction of material cutting quantity by applying a minimal number of processes. By conducting heat compression and tensile tests of the samples, we identified the physical properties of the material and used the commercial software Deform-3D to conduct a forging analysis.Findings: Based on the analysis results, we designed a combined process of hot forging and cold forging and fabricated a mold and pilot products. The fabricated pilot products were evaluated using a metal flow test, an internal defect test, a surface roughness test, etc. According to the evaluation results, no significant defect was observed, and we therefore believe it is adequate for mass production.Improvements/Applications: The complex forging method can reduce the use of material by approximately 15% compared with the hot forging and the MCT machining process. Through this study, we established a product development process using a high-precision complex forging technology.Â Â